An Analysis of Metaphor in Lana Del Rey’s Selected Song Lyrics - Fadillah, Elsa Nur; Nuriadi, N; Isnaeni, M; Baharuddin, B (Journal of Authentic Research, 2026)
The purpose of this research was to identify and describe the types of metaphor and to analyse the metaphor meanings in Lana Del Rey's selected song lyrics. This study implied a qualitative research design, focusing on the interpretation of meaning rather than statistical measurement. The data were taken from five songs, namely Born to Die, Summertime Sadness, Radio, Young and Beautiful, and Happiness Is a Butterfly, and were analyzed using Stephen Ullmann's theory of metaphor classification and a formalism approach. A total of 14 metaphorical expressions were identified across the five songs. Based on Ullmann's classification, the metaphors consist of 1 anthropomorphic metaphor, 1 animal metaphor, and 12 metaphors from concrete to abstract. These metaphors are used to express various abstract feelings such as love, sadness, happiness, fear, and emotional struggle through concrete images. The meanings of the metaphors depend on the context of the lyrics rather than the literal meanings of the words. Five main themes emerge from the metaphorical expressions: unstable love, temporary happiness, emotional pain, endurance, and personal change. These themes reflect the emotional complexity of romantic relationships, the fleeting nature of joy, the persistence through hardship, and the transformation that follows suffering. This research is expected to contribute to a better understanding of metaphorical language in song lyrics and to serve as a reference for future studies on figurative language in literary works.